A pneumatic-electrostatic nozzle to produce droplets with high level charge - Chaim, Aldemir (Pesquisa Agropecuaria Brasileira, 1998)
To evaluate the influence of the earthing system of liquid of electrostatic spraying process on the charge level of spray droplets, two internal-mixture pneumatic-electrostatic nozzles were developed, with a miniature induction-electrode totally embedded in air cap, justly in the droplet formation region. One of the nozzles (B1) had an earthed electrode constituted of a sharp-pointed metallic cylinder, embedded in the liquid duct of the nozzle body. For the other nozzle (B2), the earthing of the liquid was provided by a metallic needle embedded in the nozzle body, and whose sharp point stayed 1 mm outside of the liquid emergence orifice of the nozzle tip. The needle earthing system produced more charge in sprays than the other system, under different conditions of pressure and voltage. In other assay, the B2 nozzle produced a spray charge of 22 μC/g with a flow rate of 60 mL/min, 392 kPa of air pressure and 3,500 volts of induction voltage. This charge level is higher than those attained by other electrostatic nozzles described in literature.
Keywords: electrostatic nozzle; pneumatic nozzle; spray droplets; charged droplets